A Review on The Causative Agents, Risk Factors and Management of Ventilator-Associated Pneumonia: South Asian Perspective - Ahmed, Akash; Naboni, Nahian Sanjida; Nowshen, Afia; Sultana, Sadia; Haque, Fahim; Hossain, M Mahboob (Journal of Medicine, 2022)
Ventilator-Associated Pneumonia (VAP) is common hospital-acquired pneumonia in ICU patients. Patients with pneumonia after 48 hours of mechanical ventilation are VAP affected. INICC found that VAP rates between 2012 to 2017 are 14.1 per 1000 episodes. The most common pathogens include Acinetobacter baumannii, Pseudomonas Aeruginosa and Klebsiella pneumoniae. Developing countries seem to have a higher mortality rate compared to developed countries. Treatment protocol involves antibiotic therapy. For the early onset of VAP, cephalosporin (cefotaxime or ceftriaxone), fluoroquinolone, or piperacillin-tazobactam are found to be effective while for late-onset, ceftazidime, ciprofloxacin, meropenem, and piperacillin-tazobactam seems to have positive Results. Apart from antibiotics, other options like bacteriophage therapy can offer a good alternative to fight the rapid emergence of MDR pathogens. J MEDICINE 2022; 23: 151-161